(untitled) (Journal of the College of Basic Education, 2023)
Humanity has known since ancient times the conflicts between them throughout the ages, as the human self is built on good and evil.In the pre-Islamic era, life had a tribal feature and its society was Bedouin, governed by the customs and traditions of its desert character, and what the desert represented in terms of ruggedness, severity and brutality.The environment of the Arabs is mostly Bedouin, and the Bedouins are always nomads, following pasture, water, and rain sites wherever they are. Conflict, and because the arid environment imposes, in times of drought, a struggle over the resources of life, this life feature of the conflict has been raised from the status of (invasion) to become a state in which the Arab is proud of the heroic act. at the tramps (1)These matters led to a large number of conflicts between the tribes, so the continuous migration was one of the causes of conflicts and wars between the tribes, in addition to many other reasons, including economic and social ones, which are legitimate motives if they are put in their real framework, although there are many who overestimate the conflict and say: (( When the heavens were replaced and the earth became full, they would eat one another.” (2)The motives of the conflict can be determined according to their nature, foremost of which are the social motives based on the principle of (taking revenge), which one of the researchers says about them ((has taken hold of the Bedouin mind, which does not rest or close an eyelid before taking revenge, and the calamity is magnified when the man is not satisfied with the murderer only Rather, he is determined to exterminate the tribe.” (3).Among the other reasons for conflicts and wars is fear and a lack of a sense of security, especially in situations where wars are prolonged and genocide becomes an inherent feature, along with fear of the future that man does not know what he will gain. It is natural in humans that no nation or generation is without, and the reason for this revenge is in most cases either jealousy and competition, or aggression, or either God’s anger and his religion, or anger towards the king and his efforts to pave him...)) (4). War represents a social and political value for the Arabs through which they achieve their existenceAnd their being and strength when they feel danger and external threatWomen’s lamentations in war poetry represented a wide part of Arab life at the time because of its prominent role in igniting the fire of war due to its great position within Arab society, and because lamentation shows grief, anguish and loss, which is closer to her passion and sincerity of her feeling.